The Impact of Consumer Engagement on International Brand Building through Social Media ; A Case Study of Finnish Internationalied SMEs - Nikkinen, Larissa (My University, 2024)
Digitalization has changed our everyday lives. Consumers are spending increasingly valuable time on various social media channels, which has altered how consumers and companies interact, making it more interactive. As social media platforms continue to evolve, they have become valuable tools for creating and maintaining customer relationships and for building successful and strong brands. Consumer engagement on social media can benefit companies by allowing them to collaborate with their customers and create value together. It also gives companies valuable insights into their customers' needs. Besides, social media channels create new opportunities for companies in today's digital environment. To take advantage of these new digital developments, brands need to adopt a more dynamic way of thinking and acting to maintain a competitive edge and achieve success in the market. For this reason, social media channels provide an essential platform for brand building, enabling critical competitive advantages in international markets. Branding plays an important role in today's globalized world, where companies are beginning to expand into international markets more rapidly. Strong and distinctive brands need better positions and visibility to attract consumers and succeed in the new competitive market. Co-creation of a brand has become even more important in international markets. Co-creation in brand development is one of the key factors in creating a strong international brand. This approach is helpful for small and medium-sized enterprises (SMEs) with limited resources, as co-creation with brand stakeholders reduces constraints and benefits companies in international markets. More importantly, co-creation helps SMEs build their brands in a way that appeals to and attracts consumers. In international brand orientation, the brand's country of origin (COO) has been studied to affect consumers' perceptions and pur- chase intentions. This study explores how consumer engagement affects the international brand-building of Finnish SMEs through social media. The research is based on previous academic work that emphasizes the shift in brand-building processes from the company's control to the consumers' control, where consumers significantly influence today’s brand-building processes. The international as- pect of the research includes examining the impact of the company's country of origin on co- creating a Finnish brand with consumers on social media. Digitalisaatio on muuttanut jokapäiväistä elämäämme. Kuluttajat viettävät yhä enemmän arvokasta aikaa sosiaalisen median eri kanavissa, mikä on muuttanut kuluttajien ja yritysten vuorovaikutustapoja vuorovaikutteisemmaksi. Samalla kun sosiaalisen median alustat kehittyvät jatkuvasti, niistä on tullut arvokkaita työkaluja asiakassuhteiden luomiseen ja ylläpitämiseen sekä menestyvien ja vahvojen brändien rakentamiseen. Kuluttajien sitoutuminen sosiaalisessa mediassa voi hyödyttää yrityksiä, koska ne voivat tehdä yhteistyötä asiakkaidensa kanssa ja luoda arvoa yhdessä. Se myös antaa yrityksille arvokasta tietoa asiakkaidensa tarpeista. Lisäksi sosiaalisen median kanavat luovat uusia mahdollisuuksia yrityksille nykypäivän digitaalisessa ympäristössä. Voidakseen hyödyntää tätä uutta digitaalista ke- hitystä, brändien on omaksuttava dynaamisempi ajattelu- ja toimintatapa säilyttääkseen kilpailuetunsa ja saavuttaakseen menestystä markkinoilla. Tästä syystä sosiaalisen median kanavat tarjoavat olennaisen alustan brändin rakentamiselle, mikä mahdollistaa kriittisen kilpailuedun kansainvälisillä markkinoilla. Brändäyksellä on tärkeä rooli nykypäivän globalisoituneessa maail- massa, jossa yritykset alkavat laajentua entistä nopeammin kansainvälisille markkinoille. Menestyäkseen uusilla kilpailluilla markkinoilla vahvat ja erottuvat brändit tarvitsevat parempia asemia ja näkyvyyttä erottuakseen joukosta ja houkutellakseen kuluttajia. Brändin yhteisluominen on noussut entistä tärkeämmäksi kansainvälisillä markkinoilla. Yhteisluominen brändin ke- hittämisessä on yksi avaintekijöistä vahvan kansainvälisen brändin luomisessa. Tämä lähestymistapa on hyödyllinen pienille ja keskisuurille yrityksille (pk-yrityksille), joilla on rajalliset resurssit, koska luominen yhdessä brändin sidosryhmien kanssa vähentää rajoituksia ja hyödyttää yrityksiä kansainvälisillä markkinoilla. Vielä tärkeämpää on, että yhteisluominen auttaa pk-yrityksiä rakentamaan brändejään tavalla, joka vetoaa kuluttajiin ja houkuttelee heitä. Kansainvälisessä brändiorientaatiossa brändin alkuperämaan (COO) on tutkittu vaikuttavan kuluttajien käsityksiin ja ostoaikeisiin. Tässä tutkimuksessa selvitetään, kuinka kuluttajien sitoutuminen vaikuttaa suomalaisten pk-yritysten kansainväliseen brändin rakentamiseen sosiaalisessa mediassa. Tutkimus perustuu aikaisempaan akateemiseen tutkimukseen, jossa korostetaan brändinrakennusprosessien siirtymistä yrityksen hallinnasta kuluttajien ohjaukseen, jossa kuluttajat vaikuttavat merkittävästi nykypäivän brändinrakennusprosesseihin. Tutkimuksen kansainvälisenä näkökulmana tarkastellaan yrityksen alkuperämaan vaikutusta suomalaisen brändin luomiseen yhdessä kuluttajien kanssa sosiaalisessa mediassa.
Keywords: markkinointi; brändit; sosiaalinen media; brändäys; pienet ja keskisuuret yritykset; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business